ANALISIS PENERAPAN ARM’S LENGTH PRINCIPLE PADA TRANSAKSI PEMBAYARAN ROYALTI ATAS PEMANFAATAN MEREK DAGANG (TRADEMARK) KEPADA PERUSAHAAN AFILIASI - Hukamawati, Dinartika; Andriani, Arifah Fibri (Polytechnic of State Finance STAN, 2016)
Trademark is a unique marketing intangible. It does not only involve the expenses of marketing, advertising, and promoting, but the reputation of the trademark's owners also takes part in the development of trademark. Many parties involve in the development of trademark. In the context of transfer pricing, these parties entitle to some compensation. And arm's length principle must be applied to determine the reasonable compensation for the use of trademark. Transaction payment of royalties on trademarks is subject to taxes.The taxation of transactions payment of royalties on the use of the trademark among affiliated companies also created disputes between the taxpayer and Tax collector. Cases disputed are related to the fairness of the transaction relating to the determination of royalty payments on trademarks which cover: definition, identification, allocation and valuation between affiliated companies (Caroline Silberztein, 2010). The dispute raises the burden of the cost of compliance for taxpayers and cost of collection to the tax authorities.This study aims to determine how to identify ownership and economic benefits, as well as the best method which can be applied to determine the reasonable price of royalty payment transaction for the trademark use.The results shows that in order to determine the parties entitled to compensation/ remuneration are: Party who can be legally declared to have legal ownership (legal owner) which are parties that have control over decisions related to the exploitation of the intangible as well as the right to restrict others to use intangible; Parties that contribute to the value of the trademark by identifying the parties who bear the cost and risk of the development of the trademark.